Ephraim Amu's "Bonwere KenteÅ‹wene": a celebration of Ghanaian traditional knowledge, wisdom, and artistry - Dor, George Worlasi Kwasi (International Library of African Music, 2014)
By analyzing Amu's "Bonwere KenteÅ‹wene” (trans. "Bonwere Kente Weaving”), an art song for voice and piano, this article explores some of these paradigm-shifting processes. They include Amu's creation of the song's text as a narrative on an imaginary journey that foregrounds forms of traditional knowledge and their producers, the quest and advocacy for indigenous African knowledge, weaving of the kente cloth, the process of making a new song, construction of Ghanaian identity through composing an art song, and dissemination of knowledge involved in his process and production of a composition. I examine the major factors that informed Amu's inspiration, ingenuity, and agency that provoked this art song. These include translation of the generative power of one type of expressive art form into another expressive art form, his selectivity of pre-compositional resources, and his underpinning creative philosophy.
Keywords: African Music; Ghana; Traditional Knowledge; Wisdom; Artistry